The Significance of the words That Are Similar to Their Pronunciation, and their Wording Varied in the Holy Quran - Muhi Rebat, Shaymaa; Khorsheed Kareem, Affan (International Journal of Psychosocial Rehabilitation, 2020)
The words in the Arabic language are either names, verbs, or letters, and each name and verb has a root -a linguistic origin—to which it refers, and this linguistic root has its value in indicating a sign or indication that each of its members contains a pivotal link, then they associate it with a pivotal sign. It resembles the genes that all individuals carry, one crucifixion of all colors, shapes, and nature. So (multiplication, multiplication, multiplication, multiplication, multiplication, multiplication) is all due to the origin (multiplication), because the event is completely related to them, but the method and time distinguish between them morphological form and this is the subject of our study, was chosen on a set of words in the Holy Quran Her words were similar, and their morphological form was different, which was mentioned by Dr. Hamdi Badr Al-Din Ibrahim in his book "A Dictionary of Morphological Weights for Words." The Holy Qur’an, where it is manifested in those words that agree in the word, the eye, and confusion and is due to misleading, is the three words, the second and third letters, which are: (broadcast, Haj, right, live response, incision, repulsion, thought, count, palm, D, more, Miss, who). Therefore, when repeated by very different readers, especially non-specialists, they are confused by it and think that screaming is of the same gender; then we need a study section of those words and a statement of its type. Oaz Har's lexical and contextual equations depend on the morphological formula as mentioned in the statement. And the distinction between sexual pronunciation in addition to the indication in terms to denote Turkish morphological data for buildings, the study also aims to link the lesson morphology of the Holy Qur'an and teach through the various morphological structures of the statement; the inductive approach is circumstantial, relying on the most important sources of study and references from within our field.